Anesthesia and developing brain: What have we learned from recent studies - Niu, Yixuan; Yan, Jia; Jiang, Hong (Frontiers in Molecular Neuroscience, 2022)
Anesthesia is unavoidable in surgical procedures. However, whether the general anesthetics are neurotoxic to immature brains remains undefined. Neurodevelopmental impairment induced by anesthesia has been a critical health issue and topic of concern. This review summarizes recent progress made in clinical and preclinical studies to provide useful suggestions and potential therapeutic targets for the protection of the immature brain. On the one hand, clinical researchers continue the debate about the effect of single and multiple exposures to anesthesia on developing brains. On the other hand, preclinical researchers focus on exploring the mechanisms of neurotoxic effects of general anesthesia on immature brains and seeking novel solutions. Rodent models have always been used in preclinical studies, but it is still unclear whether the mechanisms observed in rodent models have clinical relevance. Compared with these models, non-human primates (NHPs) are more genetically similar to humans. However, few research institutions in this area can afford to use NHP models in their studies. One way to address both problems is by combining single-cell sequencing technologies to screen differential gene expression in NHPs and perform in vivo validation in rodents. The mechanism of anesthesia-induced neurotoxicity still requires further elucidation in primates.